2019
DOI: 10.1161/circresaha.118.313260
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular and Cognitive Dysfunction in Hypertension

Abstract: Hypertension has emerged as a leading cause of age-related cognitive impairment. Long known to be associated with dementia caused by vascular factors, hypertension has more recently been linked also to Alzheimer's disease, the major cause of dementia in older people. Thus, while midlife hypertension is a risk factor for late-life dementia, hypertension may also promote the neurodegenerative pathology underlying Alzheimer's disease. The mechanistic bases of these harmful effects remain to be established. Hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
339
3
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 372 publications
(359 citation statements)
references
References 205 publications
(241 reference statements)
12
339
3
5
Order By: Relevance
“…This result could be explained because stroke is a cause of VD and hypertension is a strong stroke risk factor. In several studies, antihypertensive medication use has been associated with less cognitive decline [24,34]. Our study reaffirmed that lowering blood pressure helps prevent dementia, especially VD.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This result could be explained because stroke is a cause of VD and hypertension is a strong stroke risk factor. In several studies, antihypertensive medication use has been associated with less cognitive decline [24,34]. Our study reaffirmed that lowering blood pressure helps prevent dementia, especially VD.…”
Section: Discussionsupporting
confidence: 83%
“…In a recent large trial, the FINGER study [23], a multidomain lifestyle intervention program including nutrition, exercise, and cognitive training focusing on metabolic risk management improved the cognitive function of at-risk older people. Also, cardiovascular medication, especially antihypertensive medication, showed some benefit for dementia risk [24]. Diabetes mellitus and hyperlipidemia have less evidence, however.…”
Section: Discussionmentioning
confidence: 99%
“…This vessel damage can cause elevated BP that can eventually lead to impaired cerebral blood flow. 57 In agreement with this, Kent et al, 40 found that cherry juice not only significantly improved cognitive function but also decreased systolic BP in older adults with mild-to-moderate dementia. Relatedly, Keane et al, 42 demonstrated that 60 ml Montmorency tart cherry juice concentrate acutely lowered systolic BP over a period of three hours and modulated cerebral blood flow in the prefrontal cortex of younger men with early hypertension compared to control group.…”
Section: Figmentioning
confidence: 64%
“…Emerging as a leading cause of age-related cognitive dysfunction, hypertension is known to be linked to VD, and is also associated with AD and other adverse cognitive outcomes (Crous-Bou et al, 2017;Iadecola and Gottesman, 2019). These evidences primarily come from many epidemiological studies, which strongly support the idea that hypertension is clearly correlated with steeper cognitive decline.…”
Section: Hypertensionmentioning
confidence: 95%